2012
DOI: 10.1210/en.2011-1548
|View full text |Cite
|
Sign up to set email alerts
|

TSH Regulates Pendrin Membrane Abundance and Enhances Iodide Efflux in Thyroid Cells

Abstract: Thyroid hormones are essential for normal development and metabolism. Their synthesis requires transport of iodide into thyroid follicles. The mechanisms involving the apical efflux of iodide into the follicular lumen are poorly elucidated. The discovery of mutations in the SLC26A4 gene in patients with Pendred syndrome (congenital deafness, goiter, and defective iodide organification) suggested a possible role for the encoded protein, pendrin, as an apical iodide transporter. We determined whether TSH regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 41 publications
6
47
1
Order By: Relevance
“…Thus, while increase of intracellular calcium concentration does not affect pendrin-mediated iodide efflux, it greatly stimulates iodide release from ANO1-expressing HEK 293T cells, PCCl3 cells, and dog thyrocytes. Of note, Pesce et al (27) showed weak activation of iodide loss by TSH but not by forskolin in PCCl3 cells, which suggests a TSH effect through the weakly responding phospholipase C-PIP 2 …”
Section: Concentration In Pccl3 Cells and In Ano1-expressing Hek 293tmentioning
confidence: 95%
“…Thus, while increase of intracellular calcium concentration does not affect pendrin-mediated iodide efflux, it greatly stimulates iodide release from ANO1-expressing HEK 293T cells, PCCl3 cells, and dog thyrocytes. Of note, Pesce et al (27) showed weak activation of iodide loss by TSH but not by forskolin in PCCl3 cells, which suggests a TSH effect through the weakly responding phospholipase C-PIP 2 …”
Section: Concentration In Pccl3 Cells and In Ano1-expressing Hek 293tmentioning
confidence: 95%
“…It is well known that TSH induces the expression of many genes involved in TH biosynthesis, particularly the expression of Pds and Nis and, to a lesser extent, that of Tpo and Duoxa2 (6,7,9,10,43). Since TSH levels are greatly elevated in Glis3KO mice, one might surmise that these genes are expressed at significantly higher levels in Glis3KO compared with WT mice.…”
Section: 2mentioning
confidence: 99%
“…Interaction of TSH with the TSH receptor (TSHR), a G proteincoupled receptor (Gα q /Gα 11 ), leads to activation of several kinase signaling cascades, including PKA, PKC, AMPK, and the PI3K/ mTOR complex 1 (mTORC1) pathways (2)(3)(4)(5)(6)(7)(8). Through these pathways, TSH regulates the expression of genes that are associated with thyroid gland development and TH biosynthesis and secretion, including thyroid peroxidase (TPO), and the Na + /I -symporter (NIS; SLC5A5) and iodide transporter pendrin (PDS, also referred to as SLC26A4) (7,9,10). Prolonged TSH stimulation causes proliferation of thyroid follicular cells, leading to enlargement of the thyroid gland (goiter) (6,8,11).…”
Section: Introductionmentioning
confidence: 99%
“…Using Thyr-IL-4 transgenic mice, this study showed for the first time an IL-4-dependent induction of Slc26a4 transcription, which was associated with increased apical expression of pendrin. TSH can rapidly stimulate pendrin membrane translocation via the PKA pathway (65), although the Thyr-IL-4 mice showed no significant increase in serum TSH level relative to WT mice (Fig. 2B).…”
Section: Discussionmentioning
confidence: 96%